Religion as practices of attachment and materiality: the making of Buddhism in contemporary London. Issue 3 (2nd July 2016) - Watson, Sophie; Zanetti, Oliver
Abstract: This article aims to explore Buddhism's often-overlooked presence on London's urban landscape, showing how its quietness and subtlety of approach has allowed the faith to grow largely beneath the radar. It argues that Buddhism makes claims to urban space in much the same way as it produces its faith, being as much about the practices performed and the spaces where they are enacted as it is about faith or beliefs. The research across a number of Buddhist sites in London reveals that number of people declaring themselves as Buddhists has indeed risen in recent years, following the rise of other non-traditional religions in the UK; however, this research suggests that Buddhism differs from these in several ways. Drawing on Baumann's (2002) distinction between traditionalist and modernist approaches to Buddhism, our research reveals a growth in each of these. Nevertheless, Buddhism remains largely invisible in the urban and suburban landscape of London, adapting buildings that are already in place, with little material impact on the built environment, and has thus been less subject to contestation than other religious movements and traditions. This research contributes to a growing literature which foregrounds the importance of religion in making contemporary urban and social worlds.